Poststudy Point-of-Care Oral Fluid Testing in Human Immunodeficiency Virus-1 Vaccinees. (15th December 2020) - Oganezova, Karina; Fontana-Martinez, Elvin J; Gothing, Jon A; Pandit, Alisha; Kwara, Esther; Yanosick, Katherine; Dragavon, Joan; Goecker, Erin A; Maenza, Janine; Espy, Nicole; Tomaka, Frank; Lavreys, Ludo; et al.
Abstract: Background: Experimental human immunodeficiency virus (HIV)-1 vaccines frequently elicit antibodies against HIV-1 that may react with commonly used HIV diagnostic tests, a phenomenon known as vaccine-induced seropositivity/seroreactivity (VISP/VISR). We sought to determine, under clinic conditions, whether a patient-controlled HIV test, OraQuick ADVANCE Rapid HIV-1/2 Antibody Test, detected HIV-1 vaccine-induced antibodies. Methods: Plasma assessment of HIV-1 cross-reactivity was examined in end-of-study samples from 57 healthy, HIV-uninfected participants who received a candidate vaccine that has entered Phase 2B and 3 testing. We also screened 120 healthy, HIV-uninfected, unblinded HIV-1 vaccine participants with VISP/VISR for an assessment using saliva. These participants came from 21 different parent vaccine protocols representing 17 different vaccine regimens, all of which contained an HIV-1 envelope immunogen. OraQuick ADVANCE was compared with results from concurrent blood samples using a series of commercial HIV screening immunoassays. Results: Fifty-seven unique participant plasma samples were assayed in vitro, and only 1 (1.8%) was reactive by OraQuick ADVANCE. None of the 120 clinic participants (0%; 95% confidence interval, 0% to 3.7%) tested positive by OraQuick ADVANCE, and all were confirmed to be uninfected by HIV-1 viral ribonucleic acid testing. One hundred eighteen of the 120 (98.3%) participants had a reactive HIV test for VISP/VISR: 77 (64%) had at least 1 reactive fourth-generation HIV-1 diagnostic test ( P  < .0001 vs no reactive OraQuick ADVANCE results), and 41 (34%) only had a reactive test by the less specific third-generation Abbott Prism assay. Conclusions: These data suggest that this widely available patient-controlled test has limited reactivity to HIV-1 antibodies elicited by these candidate HIV-1 vaccines. Abstract : Experimental HIV-1 vaccines frequently elicit antibodies which cross-react with common HIV diagnostic tests. Vaccine-induced seropositivity/seroreactivity (VISP/VISR) can be problematic for clinical trial volunteers. We tested a point-of-care HIV test, OraQuick ADVANCE, to determine if it could detect VISP/VISR.